Film jako instalacja. Przestrzeń, narracja i afekt w ekspozycji Mieke Bal „Madame B". - Rejniak-Majewska, Agnieszka (Artium Quaestiones, 2020)
The article discusses the construction of space and the position of the viewer in the video installation Madame B. Explorations in Emotional Capitalism, presented at the turn of 2013 at the Museum of Art in Łódź. Directed and designed by Mieke Bal and Michelle Williams Gamaker, the installation was produced in parallel with a full feature film of the same title. Both the installation and the film constitute an intersemiotic translation of a literary work – Gustave Flaubert’sMadame Bovary. Part of the inspiration for this experiment was the proto-cinematic quality of Flaubert’s style (narrative simultaneity resembling parallel editing, the suppression of drama, dissolution of the time-flow). The museum installation, with its use of dark exhibition space and multiscreen projection, provided an innovative interpretation of the novel by bringing to the fore its acute audio-visuality: the non-verbal level of meaning found in the presentation of material surroundings, fashion, gesture, facial expressions, sound, tone, and tempo of action. In this respect, the exhibition had an advantage over the continuous version of the feature film, which tends to focus the viewer’s attention more directly on the plot. In the case of the museum installation, the narrative continuity was disregarded in favor of the affective resonance of selected scenes from Emma’s life. Walking through a series of episodes split across nineteen screens, the viewer had to choose his or her own way through a complex narrative (the whole comprised 450 min. of filmic material), so in a sense it was the viewer who “performed the piece”. The narrative of Madame B. partly diverged from Flaubert’s story to bring it closer to our times. The anachronistic intermingling of the 19th century and contemporary realities set it away from the conventions of costume movies and suggested the actuality of Emma’s story – its relevance for contemporary questions of “emotional capitalism”. These anachronisms and the spatialization of the narrative occasioned a specific position for the viewer, who, despite the immersive effect of the images, remained conscious of his or her participatory presence here and now. Thus, while attending to the scenes of Emma’s life, the viewer might also reflect on the emotional effects they raised in him/herself. This analytic outlook did not necessarily inhibit the viewer’s sympathetic engagement with the protagonists’ emotions and experiences, but gave it a more informed character. The spatial arrangement of images, as well as the situations performed in several episodes, also invited reflections on the social function of looking and being seen. In this sense, the installation may be counted as a part of Mieke Bal’s practice of visual culture analysis.